Occurrence of Cassava Lace Bug Vatiga illudens (Drake, 1922) (Hemiptera: Heteroptera: Tingidae) in Bali, Indonesia - Sudiarta, I Putu; Dinarkaya, Shah Mahapati; Devi, Komang Saraswati; Ariyanta, I Putu Bawa; Wirya, Gusti Ngurah Alit Susanta; Sugiarta, Dwi; Selangga, Dewa Gede Wiryangga; Gargita, I Wayan Diksa; Wiguna, Putu Perdana Kusuma; Yuliadhi, Ketut Ayu; Devi, Putu Shinta (Universitas Gadjah Mada, 2024)
Cassava Lace Bugs (CLB) are native pest of cassava (Manihot esculenta Crantz, Euphorbiaceae) to the Neotropical Region, mainly in Brazil. On the other hand, East Java was the first region in Indonesia to record the presence of CLB in 2021, however, it has not been reported in other regions in Indonesia. Therefore, the very importance to recognise the occurrence of CLB in other regions in Indonesia. Based on this, the research has been carried out starting with a field survey, observing behaviour of insect in the field and identify morphologically in the laboratory. The survey results show that the infestation of CLB has been found in lowland, medium, and highland areas in Bali. Symptoms of infestation on the upper leaf surface are small yellow spots with brownish variations. Based on the identification key, CLB from Bali Indonesia, shows a characteristic of a head with a pair of frontal spines. Based on this evidence, the CLB insect can be identified as Vatiga illudens (Hemiptera: Heteroptera: Tingidae). It is the first report of novel distribution areas for V. illudens in Bali, Indonesia. The results of this research are important because V. illudens is one of the main pests of cassava.